In Vivo Imaging of Exogenous Progenitor Cells in Tendon Regeneration via Superparamagnetic Iron Oxide Particles. Issue 11 (September 2019) - Kremen, Thomas J.; Bez, Maxim; Sheyn, Dmitriy; Ben-David, Shiran; Da, Xiaoyu; Tawackoli, Wafa; Wagner, Shawn; Gazit, Dan; Pelled, Gadi
Background: Although tendon injuries and repairs are common, treatment of these injuries has limitations. The application of mesenchymal progenitor cells (MPCs) is increasingly used to optimize the biological process of tendon repair healing. However, clinically relevant technologies that effectively assess the localization of exogenous MPCs in vivo are lacking. Hypothesis: Exogenous MPCs labeled with superparamagnetic iron oxide (SPIO) particles would allow monitoring of the localization and retention of cells within the site of implantation via magnetic resonance imaging (MRI) without negatively affecting cell survival or differentiation. Study Design: Descriptive laboratory study. Methods: Genetically modified C3H10T1/2 MPCs engineered to express luciferase (Luc+) reporter gene were implanted into surgically created Achilles tendon defects of 10 athymic nude rats (Hsd:RH-Foxn1 rnu ). Of these animals, 5 animals received Luc+ C3H10T1/2 MPCs colabeled with SPIO nanoparticles (+SPIO). These 2 groups of animals then underwent optical imaging with quantification of bioluminescence and MRI at 7, 14, and 28 days after surgery. Statistical analysis was conducted by use of 2-way analysis of variance. At 28 days after surgery, animals were euthanized and the treated limbs underwent histologic analysis. Results: Optical imaging demonstrated that the implanted cells not only survived but also proliferated in vivo, and these cells remained viable for at least 4 weeks after implantation. In addition, SPIO labeling did not appear to affect MPC survival or proliferation, as assessed by quantitative bioluminescence imaging ( P > .05, n = 5). MRI demonstrated that SPIO labeling was an effective method to monitor cell localization, retention, and viability for at least 4 weeks after implantation. Histologic and immunofluorescence analyses of the repaired tendon defect sites demonstrated tenocyte-like labeled cells, suggesting that cell differentiation was not affected by labeling the cells with the SPIO nanoparticles. Conclusion: MRI of exogenous MPCs labeled with SPIO particles allows for effective in vivo assessments of cell localization and retention in the setting of tendon regeneration for at least 4 weeks after implantation. This SPIO labeling does not appear to impair cell survival, transgene expression, or differentiation. Clinical Relevance: SPIO labeling of MPCs appears to be safe for in vivo assessments of MPCs in tendon regeneration therapies and may be used for future clinical investigations of musculoskeletal regenerative medicine.